2008
DOI: 10.1002/mrm.21531
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 exacerbates focal cerebral ischemia and reduces ischemic brain temperature in the rat

Abstract: The proinflammatory cytokine interleukin-1 (IL-1) is a key mediator of inflammation in cerebral ischemia, but its precise mechanisms of action remain elusive. Temperature is critical to outcome in brain injury and given the importance of IL-1 in pyrogenesis this has clear mechanistic implications. IL-1 exacerbates ischemia independently of core (rectal) temperature. However, it is temperature in the ischemic brain that influences outcome and rectal temperature is likely to be a poor surrogate marker. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…It is also thought that focal ischemia of the brain is a pro-inflammatory stimulus and that interactions of inflammatory cytokines with components of the neurovasculature are in response to BBB permeability [23]. Our studies supported this hypothesis and identified IL-1β as a stimulus of endothelial permeability, which has been previously postulated to facilitate edema formation during the initial moments following the onset of focal ischemia [35], [36]. On the basis of these results, we conjectured that morroniside regulated cerebrovascular permeability after stroke via the downregulation of MMPs and IL-1β, hence inhibiting edema formation during the initial phase.…”
Section: Discussionsupporting
confidence: 81%
“…It is also thought that focal ischemia of the brain is a pro-inflammatory stimulus and that interactions of inflammatory cytokines with components of the neurovasculature are in response to BBB permeability [23]. Our studies supported this hypothesis and identified IL-1β as a stimulus of endothelial permeability, which has been previously postulated to facilitate edema formation during the initial moments following the onset of focal ischemia [35], [36]. On the basis of these results, we conjectured that morroniside regulated cerebrovascular permeability after stroke via the downregulation of MMPs and IL-1β, hence inhibiting edema formation during the initial phase.…”
Section: Discussionsupporting
confidence: 81%
“…Acute peripheral inflammatory challenge worsens outcome after focal cerebral ischemia (McColl et al, 2007a) and increases hippocampal neuronal death after global cerebral ischemia (Spencer et al, 2007). These effects are independent of core body and brain temperature (Parry-Jones et al, 2008). Systemic inflammation also sensitizes the brain to neonatal hypoxic and hemorrhagic injury (Lehnardt et al, 2003;Xue and Del Bigio, 2005) and exacerbates excitotoxic (Favrais et al, 2007) and traumatic brain injury (Utagawa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the infarct core, reduced blood flow induces the reduction of heat radiation and increased anaerobic metabolism induces the increase in heat production, which may both result in the elevated brain temperature. In IP tissue, reduced blood flow may induce the reduction of heat radiation, while an increase in heat production is induced by the subsequent events, including both aerobic and anaerobic metabolism [1922], inflammation and the release of excitatory amino acids [23, 24]. These complex processes may account for the higher elevated brain temperature in the IP than in the infarct core or oligemic regions at the artery occlusion stage.…”
Section: Discussionmentioning
confidence: 99%